Optimalisasi Peran Kepala Sekolah dalam Pendampingan Guru Menangani ABK Disleksia: Studi Kasus di SDN SOKO - Leny Kurniawati; Liftiah Liftiah; Ali Formen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the optimization of the principal's role in assisting a classroom teacher to handle a dyslexic student at SDN SOKO. Dyslexia affects 10–15% of elementary school children in Indonesia, yet many teachers lack training and principals limit their role to administrative duties. A qualitative case study method was employed, involving the principal (researcher), teacher (WEM), and dyslexic student (AI). Data were collected through interviews with teacher WEM and AI's parents, three months of classroom observations, and documentation. Data analysis followed Miles, Huberman, and Saldaña's interactive model, with triangulation ensuring validity. The findings reveal five optimized roles of the principal: manager (forming inclusion team, allocating budget for multisensory media), supervisor (clinical supervision every two weeks), facilitator (internal training, quiet reading corner), communicator (monthly parent-teacher-principal meetings), and motivator (reward certificates for AI, public appreciation for teacher WEM). Consequently, AI's reading accuracy improved from 20/100 to 65/100, and letter reversal errors decreased by 70% within three months. The study concludes that an active, systematic principal role significantly enhances teacher competence and dyslexic students' reading ability.